Identificación preliminar de las principales especies de mosca de la fruta y sus hospederos en Ongón, Pataz, La Libertad. - Rivera Roldan, Henrry Edinson (2017)
The objective of this research work was to identify the main species of fruit fly, as well as their hosts in Ongón, Pataz, La Libertad. To this end, in the agricultural sectors of the area, Jackson traps were placed for the capture of males of the species Ceratitis capitata; and Multilure traps for the capture of adults of the genera Anastrepha spp. and Ceratitis capitata. The identification of Ceratitis capitata W. was carried out visually with the help of a magnifying glass at the field level and the Anastrepha species,in the laboratory using the Fruit Fly Identification Manual of Korytkowski and the Field Guide for the Recognition of Fly the Fruit of the Anastrepha Genus (Mexico, 2010).For the identification of the hosts, weekly, within a radius of approximately 50 meters from the location of the traps, the fruits of the different species of commercial crops and wild species were collected and by means of dissection was evaluated the presence of the immature stages of the pest in the fruits. The species of fruit flies identified were: Ceratitis capitata Wied. , Anastrepha fraterculus, Anastrepha striata, Anastrepha distincta, Anastrepha chiclayae, Anastrepha serpentina and Anastrepha tecta and as hosts chili, anona, coffee, caigua, chirimoya, granadilla, guanábana, guava, sweet lime, sweet lemon, rough lemon, subtle lemon, tangerine , mango criollo, passion fruit, peach, sweet orange, medlar, walnut, avocado, papaya, rocoto, tomato and grapefruit.